2019
DOI: 10.1101/753350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does rehearsal matter? Left anterior temporal alpha and theta band changes correlate with the beneficial effects of rehearsal on working memory

Abstract: There is a rich behavioral literature on articulatory rehearsal for verbal stimuli, suggesting that rehearsal may facilitate memory, but few studies have examined the benefits for visual stimuli.Neural delay period studies have largely failed to control for the use of maintenance strategies, which make activity patterns during maintenance difficult to interpret. Forty-four participants completed a modified Sternberg Task with either novel scenes (NS) that contained semantic information or phase-scrambled scene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Lower beta band ERD has also been associated with semantic processing (Hanslmayr et al, 2009), so alpha and low beta band activity may reflect complementary processes (Pavlov & Kotchoubey, 2020). Thus, the ERD observed in the latter half of the delay period of this experiment likely reflects preparation for the upcoming proberesponse through an extended period of maintenance (Plaska et al, 2021). As the same type of stimuli were used in both WM conditions this observed pattern of delay activity during the continued period of extended maintenance reflects similar processes regardless of load.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Lower beta band ERD has also been associated with semantic processing (Hanslmayr et al, 2009), so alpha and low beta band activity may reflect complementary processes (Pavlov & Kotchoubey, 2020). Thus, the ERD observed in the latter half of the delay period of this experiment likely reflects preparation for the upcoming proberesponse through an extended period of maintenance (Plaska et al, 2021). As the same type of stimuli were used in both WM conditions this observed pattern of delay activity during the continued period of extended maintenance reflects similar processes regardless of load.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, studies have found that the automatic recoding of verbalizable stimuli, such as the naturalistic scenes used in this experiment, will occur even without explicit instructions to do so (Postle et al, 2005). Rehearsal is not an attention-demanding process that will interfere with maintenance of visual information (Vergauwe et al, 2014), but linking semantic associations during rehearsal with visual information which may occur with complex naturalistic scenes (Plaska et al, 2021), may capture attentional resources. If processing and linking of semantic associations occurs during maintenance, then interference may not have occurred because any available attentional resources would be used up and not available to process the distractors.…”
Section: Delay Activity and Interferencementioning
confidence: 78%
See 1 more Smart Citation